Kepemimpinan Transformasional Kristen dan Manajemen Perubahan Organisasi Gereja - Agustina Bura; Mirayanti Sarungngu; Rini Ta'diampang; Alvina Ratte; Jupril Jupril; Trivena Punu (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Christian transformational leadership offers an ideal model for church organizational development, but its implementation in the Indonesian context faces complex structural and cultural barriers. This study aims to identify and analyze the structural and cultural barriers that influence the implementation of Christian transformational leadership in Indonesian church organizations, analyze the mechanisms of organizational resistance and their implications for leadership effectiveness, and formulate adaptive strategies relevant to local dynamics. The method used is a qualitative literature study with a systematic literature review approach of the latest academic sources. The results show that structural barriers include limited human resource capacity, weak organizational infrastructure, and immature management systems, while cultural barriers are rooted in strong local traditions and resistance to new leadership models. Organizational resistance arises through mutually reinforcing interpersonal, organizational, and cultural mechanisms, resulting in decreased congregation participation and empowerment effectiveness. Effective adaptive strategies include participatory dialogue communication, continuous leadership development, acculturation of leadership to local values, and the formation of an inclusive organizational culture. This study concludes that the sustainable implementation of Christian transformational leadership requires a holistic approach that integrates changes in structure, culture, and interpersonal relationships while remaining sensitive to the local context and cultural wisdom.